2014
DOI: 10.1016/j.calphad.2014.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Stability of 41 metal–boron systems at 0GPa and 30GPa from first principles

Abstract: A multitude of observed boron-based materials have outstanding superconducting, mechanical, and refractory properties. Yet, the structure, the composition, and the very existence of some reported metal boride (M-B) compounds have been a subject of extensive debate. This density functional theory work seeks to set a baseline for current understanding of known metal boride phases as well as to identify new synthesizable candidates. We have generated a database of over 12,000 binary M-B entries for pressures of 0… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
69
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(84 citation statements)
references
References 202 publications
(313 reference statements)
14
69
1
Order By: Relevance
“…Indeed, Kolmogorov et al [39] found that in the case of FeB 2 an orthorhombic structure, oP12, is more stable than the other structures. The results presented in Table 2 are in agreement with the results published by Van der Geest and Kolmogorov [14]. The discrepancies observed with the experimental investigations have already been discussed by these authors.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…Indeed, Kolmogorov et al [39] found that in the case of FeB 2 an orthorhombic structure, oP12, is more stable than the other structures. The results presented in Table 2 are in agreement with the results published by Van der Geest and Kolmogorov [14]. The discrepancies observed with the experimental investigations have already been discussed by these authors.…”
Section: Resultssupporting
confidence: 82%
“…The characteristics of the structures considered in the present work are given in Table 1 [5][6][7][8][9][10][11][12][13]. [14]. Indeed, these authors have recently investigated a large number of binary boron alloys.…”
Section: Introductionmentioning
confidence: 99%
“…Unexpectedly, our frozen phonon calculations 39,40 revealed that the family of Li 2n B 1D m phases across a large composition range becomes dynamically unstable under moderate pressures, a behavior not recognized in previous ab initio studies 17,[27][28][29][30]47,48 . Construction of most stable derived structures is a known challenge due to the possibility of multiple local minima with similar energies/enthalpies 43,49,50 .…”
Section: Stability Analysis and Prediction Of Derived Phases Witmentioning
confidence: 82%
“…While the present paper was under review, the same structure was proposed as the ground state structure for MnB 4 based on theoretical calculations [34] and determined experimentally [35] for normal-pressure synthesized MnB 4 crystals.…”
Section: A Crystal Structurementioning
confidence: 99%